RESISTANCE EXERCISE TO IMPROVE IMMUNE OF ELDERLY IN NEWNORMAL ERA: REVIEW LITERATURE - Cahyaningsih, Andika Nur; Widyastuti, Zulanda Indah; Febrianti, Lusi; Ramadhani, Alinda Nur (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Introduction – The high rate of transmission of Covid-19 in Indonesia has brought enormous changes to society, especially with the applied of new normal regulation. New normal regulation requires the public to continue carrying out their usual activities by implementing health protocols. The elderly are a population with high risk of covid-19 transmission. Various efforts can be made to maintain the immune system in the new normal era, one of them is by doing exercise. One of the exercises that can be done by the elderly is resistance exercise. Purpose – The purpose of this study was to identify the effect of resistance exercise to increase immunity in the elderly based on evidence based. Methodology/Approach – This study is a literature study that summarizes some relevant literature on the same theme. Literature search using 3 databases: Pubmed, Pedro and BMC Central. Key words used in the literature search included: "immune system", "resistance exercise" and "elderly". Findings – Based on the results of the literature review, it was found that resistance exercise can increase immunity in the elderly. The form of resistance exercise are: horizontal leg press, knee extension, knee flexion, horizontal supine, triceps extension pulley, biceps curl, sitting row, plantar flexion, shoulder press, hip flexion-extension. Originality/ Value/ Implication – The elderly can perform resistance exercise regularly to increase immune system during new normal era.